6 CT reports in suspected acute aortic syndrome?– audit failure to improve reporting accuracy. (18th May 2017) - Dreisbach, John; Garnett, Philip; Corbally, Conal; Roditi, Giles
Abstract : Introduction: Acute aortic syndrome (AAS) is a life-threatening condition, which requires timely and accurate diagnosis, typically by CT angiography. Experience of significant radiological discrepancies relating to CT reports in patients with AAS has driven an audit of the accuracy of CT reports. Methods: Retrospective automated electronic search of all CT reports containing the term 'dissection' over three audit cycles, covering a 4-year period (January 2013 to December 2017), across a Health Board covering over a million people with 116 consultant radiologists. Interventions consisted of presentation of audit results, discrepancies and education. The first, second and third audit cycles covered periods of 27, 12 and 9 months, respectively. CT images and reports were systematically assessed with consensus to identify cases of AAS and radiological discrepancies in reports. Results: A total of 32% (n=35/110) of reports contained at least one major discrepancy over the 4-year period, with rates of 31% (n=20/65), 26% (n=5/19) and 38% (10/26) in each of the three audit cycles. Errors consistently related to non-cardiac-gated scans, accurate diagnosis, correct classification, plus detection of haemorrhagic and malperfusion complications. Conclusion: The review consistently demonstrated major deficiencies in the radiological interpretation of suspected AAS on CT scans over three audit cycles, significant in both number and grade. Further research is required to fully assess the clinical significance the radiological errors identified. Efforts to improve local practice will continue and include wide dissemination of results, further education and encouragement to involve a specialist in cardiovascular imaging in suspected cases.